2019
DOI: 10.1017/s1755773919000080
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking political distrust

Abstract: Increasing political distrust has become a commonplace observational remark across many established democracies, and it is often used to explain current political phenomena. In contrast to most scholarship that focuses solely on the concept of trust and leaves distrust untheorized, this article makes a contribution by analysing political distrust. It argues that citizen distrust of government and political institutions poses a threat for democratic politics and clarifies the relationship between the distrust o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 57 publications
2
71
0
3
Order By: Relevance
“…Governments can hardly govern effectively when large parts of the citizenry distrust them. Political distrust contributes to limiting citizens' compliance to government rules and cutting ties with political agents and processes (Bertsou, 2019). However, there are other factors that affect citizens' compliance to government rules and their cutting ties with political agents and processes.…”
Section: Conceptualising Political Distrust In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Governments can hardly govern effectively when large parts of the citizenry distrust them. Political distrust contributes to limiting citizens' compliance to government rules and cutting ties with political agents and processes (Bertsou, 2019). However, there are other factors that affect citizens' compliance to government rules and their cutting ties with political agents and processes.…”
Section: Conceptualising Political Distrust In Nigeriamentioning
confidence: 99%
“…They include education, personal well-being, social status, dislike of politics and ideological positioning (Norris, 2011). The major drivers of political distrust are poor quality of governance, technical incompetence, poor economy performance, manipulation of reports in government-owned media, mutual suspicions, lack of basic needs, political corruption and general exclusion (Bertsou, 2019;Carlisle, 2020;Clark, 2016;Iroghama, 2012;Khan, 2016;Kress et al, 2016;Rafaty, 2018). Lee and Lee (2018) also noted that incongruent ecological worldview could promote political distrust.…”
Section: Conceptualising Political Distrust In Nigeriamentioning
confidence: 99%
“…Political distrust refers to a relational attitude that reflects the perception of distrust of a political system as a whole or its components (Bertsou, 2019). In this study, political distrust is the lack of trust in political institutions that was measured via 4 items on a 4-point Likert scale.…”
Section: Political Distrustmentioning
confidence: 99%
“…Many democracies have witnessed growing challenges to their political processes, with citizens becoming increasingly weary and distrustful of their politicians, turning their backs to established political parties and candidates or even taking to the streets to actively protest against policies and political institutions. Given the current political climate and the uninterrupted trend of deteriorating signs of system support, there is strong reason to believe that attitudes of distrust merit closer analysis [4,19]. The theoretical importance of political trust for the effective governance and legitimacy of democratic regimes has been highlighted by numerous scholars [3,5,20,21] and empirical studies have shown political trust is a key component of diffuse support for democratic systems [10,22,23].…”
Section: Dealing With Political Distrustmentioning
confidence: 99%
“…Since then, the debate rages on. Is distrust an ominous sign for democratic stability, simply an expression of dissatisfaction towards underperforming incumbents or an inevitable by-product of rising citizen expectations [3,4]? From the rich academic literature that has ensued, we know that political trust represents "a reservoir of good-will" that helps maintain support for overall democratic achievements in times of crises and that widespread political distrust can pose a fundamental challenge for the effective operation of government [5,6].…”
Section: Introductionmentioning
confidence: 99%